The ecology of automated market makers - Annetta Ho; Cosmin Cazan; Andrew Schrumm (Bank of Canada, 2024)
This paper describes the ecology of automated market makers (AMMs), which are the most popular decentralized exchange model for the pricing and trading of crypto assets within decentralized finance. We use blockchain data to identify trends in user adoption and trading volumes of AMMs. Given the range of AMMs available and the diversity of their designs, we perform case studies on four platforms-Uniswap, Curve, Sushiswap and Balancer-to represent the AMM market. We describe the designs of these four AMMs in terms of their products or services, governance, incentives for participation and risks. Finally, we describe the characteristics of AMMs that require considerations with respect to the application of a regulatory framework to AMMs. Findings are presented for information and do not represent any formal legal analysis or opinion.
Keywords: G; G1; G2; 330; Digital currencies and fintech; Financial markets; Financial stability; Financial system regulation and policies